Supramolecular approaches to metal-organic gels using 'Chevrel-type' coordination clusters as building units. - SCHMITT, WOLFGANG (My University, 2013)
A novel hexanuclear {Mn6} coordination complex with octahedral topology has been prepared and was subsequently used as a building unit for the construction of coordination polymers and metal-organic gels; the latter exhibit thixotropic behavior and reversible sol-gel phase transitions
PUBLISHED
Keywords: Chemistry